Analisa Perbandingan Implementasi Algoritma Set Partitioningin Hierarchical Trees (Spiht) Dan Boldi Vigna Code Untuk Kompresi File Audio - Ovirman Lawolo; Rivalry Kristianto Hondro; Kurnia Ulfa (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Compression is a technique used for data transmission and storage to change the initial data size to a smaller size so that the storage space is not too large. In the data compression process there are two techniques that can be used to change the file size, namely lossy and lossless. Audio files are one of the files that are often used in transmitting data. Audio files generally have a very large size so that it will make it difficult to transmit data and store data. Therefore it is necessary to compress data to reduce its size so that it is easier to overcome problems related to data transmission and data storage. In the compression process there are various methods and have different ratio results. Therefore, in this study a comparison was made between the Set Partitioning In Hierarchical Trees (SPIHT) algorithm and the Boldi Vigna Code method for audio to determine the results of a smaller and more effective compression ratio for compressing audio files. The results of the study concluded that the comparison calculation between the Set Partitioning In Hierarchical Trees (SPIHT) algorithm and Boldi Vigna Code ratio on audio file compression resulted in a value of 21.8% for the Set Partitioning In Hierarchical Trees (SPIHT) algorithm and 68.75% for the Set Partitioning In Hierarchical Trees (SPIHT) method. Code Boldi Vigna algorithm.